Informal learning in vocational education and training : illuminating an elusive concept - Pilz, Matthias [Herausgeber] (Springer VS, 2024)
"Entering educational debate more than 50 years back, the notion of informal learning is still highly relevant today and of specific interest in the context of vocational education and training (VET). Still, we do not know a lot about a wide range of aspects of the topic as well as interactions between formal and informal learning. Defining the latter precisely presents difficulties to the world of research, as the concept itself is characterised by flexibility and openness. This book was initiated to fill a gap in understanding informal learning in the context of training and development. 18 chapters cover a wide range of aspects and different objectives, levels and places of informal learning. Authors from different parts of Europe as well as Japan, Australia, India and Bangladesh have been selected to contribute to the topic from varying country perspectives. As such, this volume makes a unique contribution in exploring informal learning in VET." (Publisher, BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; S 1 Stufen der Berufsbildung; I 2.2.1 Westeuropa; I 2.2.2 Osteuropa; I 2.3.1 Afrika; I 2.3.4 Asien; I 2.3.5 Australien, Ozeanien; 370; Informelles Lernen; Berufsbildung; Berufsbildungssystem; Lehrerbildung; Anerkennung; Kompetenzbewertung; Australien; Bangladesch; Bundesrepublik Deutschland; England; Estland; Ghana; Indien; Japan; Malaysia; Nigeria; Polen; Saudi-Arabien; Spanien; Südafrika; Togo; Türkei; Ungarn